1955
DOI: 10.1161/01.res.3.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Fibrillation Induced and Maintained in Animals by Acetylcholine or Vagal Stimulation

Abstract: With the technical assistance of Robert D. Campo Animals pretreated with appropriate closes of anticholinesterase agents develop auricular flutter and fibrillation following injection of acetylcholine or vagal stimulation. Depression of normal sinoauricular nodal function facilitates induction of fibrillation. During fibrillation, additional injections of acetylcholine, or vagal stimulation, increase the rate of fibrillation. Atropine in small closes reverts the fibrillation to normal sinus rhythm.T HE product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

1962
1962
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…[11][12][13][14]38 Vagal modulation manifests as rapid oscillation in heart rate, especially as quantified by pNN50 and rMSDD. 29 Thus, the high RR interval variations observed in the high RR interval variability group are consistent with heightened vagal tone, perhaps reflex in origin, as a result of sustained perioperative sympathetic activation or accentuated antagonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14]38 Vagal modulation manifests as rapid oscillation in heart rate, especially as quantified by pNN50 and rMSDD. 29 Thus, the high RR interval variations observed in the high RR interval variability group are consistent with heightened vagal tone, perhaps reflex in origin, as a result of sustained perioperative sympathetic activation or accentuated antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 Autonomic nervous system perturbations may enhance vulnerability to atrial arrhythmias. 5,[11][12][13][14] Analysis of HRV has been used to probe autonomic mechanisms of ventricular tachycardia and fibrillation and to identify patients at risk for ventricular arrhythmias. [15][16][17][18][19][20] Preliminary investigations in primarily nonsurgical populations have suggested that risk for AF may be identified with measurement of HRV, but whether the onset of postoperative AF is preceded by autonomic dysfunction is not clear.…”
mentioning
confidence: 99%
“…Various animal models of AF have been developed to study AF substrate. Parasympathetic stimulation (either with direct vagal nerve stimulation or circulating cholinergic agents) results in shortening of atrial refractoriness and sustained AF (10,16). Prolonged rapid atrial pacing (RAP) leads to shortening of refractoriness and sustained AF (18,30).…”
mentioning
confidence: 99%
“…6,19,20 Yue et al showed that atrial rapid pacing reduced transient outward currents (Ito) and L-type Ca 2+ currents (ICa), and that the reduced ICa abbreviated APD and decreased accommodation to changes in rate. 21 It is well known that vagal tone is one of the most important factors in the induction of AF [9][10][11][12][13][14][15] and this induction of AF by VS might be caused by nonuniform shortening of the atrial ERP; 9-11 it may also increase ERP dispersion. 11 Cardiac vagal tone declines with age, 22,23 the smaller tachycardiac response to isometric exercise in older humans is associated with an inability to decrease cardiac vagal tone below an already reduced baseline level.…”
Section: Discussionmentioning
confidence: 99%